Investigating the Effect of Comprehensive Therapeutic Exercise on Cognitive and Motor Performance in People with Parkinson Disease - Z Sadaghiyani; N Tahan; A Shoeibi; S Nazary Moghadam; A.R Akbarzadeh Baghban; A Zeinalzadeh (Journal of Paramedical Science and Rehabilitation, 2025)
Propose:The purpose of this study is to investigate the effect of comprehensive exercise therapy on cognitive and motor performance in patients with Parkinson's disease.Methods:Twenty individuals (15 male, 5 female) with Parkinson's disease (age range: 62.30±9.48 years, weight: 70.40±10.20 kg, height: 166.55±8.63 cm) participated in quasi-experimental study. Before the start of the intervention, the Montreal cognitive assessment questionnaire was completed by the each participant, and functional tests including time up and go test (TUG), time up and go test motor (TUGM) and cognitive (TUGC) were taken from the participants. These tests were also taken from the participants after all sessions. The course of therapeutic exercise included 16 one-hour sessions that took place 4 times a week for one month. The data were analyzed using the paired t-test and SPSS version 20 software at a significance level of 0.05.Result:In the present study, a statistically significant improvement was observed on cognitive and motor performance. The results of the paired t-test showed that there is a significant difference in the scores of the Montreal Cognitive Assessment Questionnaire before and after the treatment (p<0.001). Also, the results of three functional tests of TUG, TUGM and TUGC before and after treatment showed statistically significant differences (p<0.001).Conclusion:Application of comprehensive therapeutic exercises in physiotherapy can help improve the cognitive and motor performance of patients with Parkinson̕ disease.